Rearrangement of immunoglobulin light chain genes in the chicken occurs prior to colonization of the embryonic bursa of Fabricius. - Mansikka, A (1990)
We have applied polymerase-chain-reaction-directed immunoglobulin gene analysis to study the embryonic differentiation of chicken B cells. Immunoglobulin light chain DNA segments in the rearranged configuration were amplified from cells of the intraembryonic mesenchyme as early as day 7 of incubation. We showed by sequencing that the rearranged variable region genes in these early B-cell progenitors were not different from the germ-line V lambda 1 gene (the single functional light chain variable region gene in chickens). In the bursal B lymphocytes, on the other hand, clear gene conversion events were first observed at day 15 of embryonic development. The present data indicate that rearrangement of light chain genes in the chicken occurs independently of the bursa of Fabricius and that diversification of the variable region begins only later, when the surface immunoglobulin-positive B cells are proliferating in the bursal follicles.